Synthesis, characterization, and evaluation of poly (D,L-lactide-co-glycolide)-based nanoformulation of miRNA-150: potential implications for pancreatic cancer therapy - Arora S (Dove Medical Press, 2014)
Sumit Arora,1 Suresh K Swaminathan,2 Ameya Kirtane,2 Sanjeev K Srivastava,1 Arun Bhardwaj,1 Seema Singh,1 Jayanth Panyam,2 Ajay P Singh1,3 1Department of Oncologic Sciences, Mitchell Cancer Institute, University of South Alabama, Mobile, Alabama, USA; 2Department of Pharmaceutics, The University of Minnesota, Minneapolis, USA; 3Department of Biochemistry and Molecular Biology, College of Medicine, University of South Alabama, Mobile, Alabama, USA Abstract: MicroRNAs are small (18–22 nucleotide long) noncoding RNAs that play important roles in biological processes through posttranscriptional regulation of gene expression. Their aberrant expression and functional significance are reported in several human malignancies, including pancreatic cancer. Recently, we identified miR-150 as a novel tumor suppressor microRNA in pancreatic cancer. Furthermore, expression of miR-150 was downregulated in the majority of tumor cases, suggesting that its restoration could serve as an effective approach for pancreatic cancer therapy. In the present study, we developed a nanoparticle-based miR-150 delivery system and tested its therapeutic efficacy in vitro. Using double emulsion solvent evaporation method, we developed a poly (D,L-lactide-co-glycolide) (PLGA)-based nanoformulation of miR-150 (miR-150-NF). Polyethyleneimine (a cationic polymer) was incorporated in PLGA matrix to increase the encapsulation of miR-150. Physical characterization of miR-150-NF demonstrated that these nanoparticles had high encapsulation efficiency (~78%) and exhibited sustained release profile. Treatment of pancreatic cancer cells with miR-150-NF led to efficient intracellular delivery of miR-150 mimics and caused significant downregulation of its target gene (MUC4) expression. Inhibition of MUC4 correlated with a concomitant decrease in the expression of its interacting partner, HER2, and repression of its downstream signaling. Furthermore, treatment of pancreatic cancer cells with miR-150-NF suppressed their growth, clonogenicity, motility, and invasion. Together, these findings suggest that PLGA-based nanoformulation could potentially serve as a safe and effective nanovector platform for miR-150 delivery to pancreatic tumor cells. Keywords: PLGA nanoparticles, miR-150, MUC4, invasion, migration